Effect of photodynamic therapy on microorganisms responsible for dental caries: A systematic review and meta-analysis - de Oliveira, Analú Barros [UNESP]; Ferrisse, Túlio Morandin [UNESP]; Marques, Raquel Souza [UNESP]; de Annunzio, Sarah Raquel [UNESP]; Brighenti, Fernanda Lourenção [UNESP]; Fontana, Carla Raquel [UNESP] (MDPI, 2019)
The aim of this study was to perform a systematic review of the literature followed by a meta-analysis about the efficacy of photodynamic therapy (PDT) on the microorganisms responsible for dental caries. The research question and the keywords were constructed according to the PICO strategy. The article search was done in Embase, Lilacs, Scielo, Medline, Scopus, Cochrane Library, Web of Science, Science Direct, and Pubmed databases. Randomized clinical trials and in vitro studies were selected in the review. The study was conducted according the PRISMA guideline for systematic review. A total of 34 articles were included in the qualitative analysis and four articles were divided into two subgroups to perform the meta-analysis. Few studies have achieved an effective microbial reduction in microorganisms associated with the pathogenesis of dental caries. The results highlight that there is no consensus about the study protocols for PDT against cariogenic microorganisms, although the results showed the PDT could be a good alternative for the treatment of dental caries.
Keywords: Antimicrobial; Dental caries; Microorganism; Photodynamic therapy; Systematic and meta-analysis review